DISPARITAS PUTUSAN HAKIM DALAM KASUS TINDAK PIDANA PENCEMARAN NAMA BAIK MELALUI FACEBOOK - Divania Ansa Salsabila (2022)
The large number of Facebook users, is misused by several parties to commit various criminal acts, such as for example committing fraud, broadcasting shows that contain pornographic acts, forgeries, and deliberate acts that cause humiliation or defamation. The purpose of the study was to determine the cause of the disparity of judges' decisions in defamation cases through Facebook and to examine defamation regulations through Facebook in order to minimize disparities in decisions. The type of research used in this research is normative legal research, the research approach used is the statutory approach, case approach and conceptual approach. The data sources used in this study are primary legal materials, secondary legal materials, and tertiary legal materials. The method of collecting data is by means of a documentation study. The data analysis technique used is qualitative data analysis techniques. The results of the study show that the disparity of criminal acts is caused by several factors from the judge's considerations, namely aggravating and mitigating matters, besides that the judge also considers the results of community research in making his criminal decisions. In addition, the judge in passing a criminal decision is not bound by the previous judge's decision, which means that the judge is not obliged to follow the previous judge's decision. To minimize the occurrence of disparities, namely by making a Government Regulation in Lieu of Law (Perppu) or making a Supreme Court Regulation (Perma) regarding guidelines for imposing criminal offenses against criminal acts of defamation through cyberspace. Keywords: Facebook; Defamation; Decision Disparity